1981
DOI: 10.1111/j.1095-8649.1981.tb05807.x
|View full text |Cite
|
Sign up to set email alerts
|

The blood cells of the Antarctic icefish Chaenocephalus aceratus Lönnberg: light and electron microscopic observations

Abstract: Peripheral blood and haemopoietic tissues of spleen and kidney of the icefish, Chaenocephalus aceratus were examined using LM and EM techniques. The peripheral blood contained cellular elements from all the recognized cell lines usually seen in other teleost groups. Erythrocytes were very rare; when found, they were mature or senile and fragile. Thrombocytes of two morphologies, several cell types considered to be part of the lymphoid series and monocytes/macrophages were present. Two distinctive types of gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…The thrombocyte of D. labrax contains an oval or round nucleus with a characteristic distribution pattern of condensed chromatin as in other fish (FERGUSON, 1976 ;BARBER and WESTERMANN, 1981;SAVAGE, 1983). The environment seems to affect cytoplasmic granulation in thrombocytes (GARDNER and YEVICH,1969).…”
Section: Thrombopoiesismentioning
confidence: 99%
“…The thrombocyte of D. labrax contains an oval or round nucleus with a characteristic distribution pattern of condensed chromatin as in other fish (FERGUSON, 1976 ;BARBER and WESTERMANN, 1981;SAVAGE, 1983). The environment seems to affect cytoplasmic granulation in thrombocytes (GARDNER and YEVICH,1969).…”
Section: Thrombopoiesismentioning
confidence: 99%
“…Furthermore, the oxygen-carrying capacity of C. aceratus blood was approximately 10% that of two red-blooded notothenioids. Subsequent investigations extended these observations to other icefish species and revealed that icefish blood contains small numbers of "erythrocyte-like" cells that, nevertheless, are devoid of hemoglobin (2,3). Thus, limited to oxygen physically dissolved in their blood, the icefishes have evolved compensatory physiological and circulatory adaptations-e.g., modest suppression of metabolic rates, enhanced gas exchange by large, well-perfused gills and cutaneous respiration, and large increases in cardiac output and blood volume-that ensure adequate oxygenation of their tissues (4,5).…”
mentioning
confidence: 99%
“…Although icefish blood contains "erythrocyte-like" cells in small numbers (2,3), these cells are devoid of hemoglobin, and icefishes transport oxygen to their tissues solely in physical solution. In the cold (Ϫ1.86 to ϩ1°C), stable, and oxygen-rich environment experienced by these organisms, reduction of the hematocrit to near zero may have been selectively advantageous because it significantly diminishes the energetic cost associated with circulation of a highly viscous, corpuscular blood fluid (4 -7).…”
mentioning
confidence: 99%